2007
DOI: 10.1063/1.2801704
|View full text |Cite
|
Sign up to set email alerts
|

Defect related issues in the “current roll-off” in InGaN based light emitting diodes

Abstract: Defect related contributions to the reduction of the internal quantum efficiency of InGaN-based multiple quantum well light emitting diodes under high forward bias conditions are discussed. Screening of localization potentials for electrons is an important process to reduce the localization at high injection. The possible role of threading dislocations in inducing a parasitic tunneling current in the device is discussed. Phonon-assisted transport of holes via tunneling at defect sites along dislocations is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
164
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(165 citation statements)
references
References 31 publications
1
164
0
Order By: Relevance
“…At high injection the localization potentials are screened, and the carriers are free to move to defect sites. 4 Other authors have shown using high resolution scanning near-field optical microscopy techniques, which the dislocations themselves are protected from nonradiative recombination events by local potentials for the violet InGaN LEDs, under the conditions of these experiments. 6 This property leaves them inactive in carrier recombination, unless these potentials are screened by carriers at higher injection levels.…”
Section: Dislocation Related Droop In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…At high injection the localization potentials are screened, and the carriers are free to move to defect sites. 4 Other authors have shown using high resolution scanning near-field optical microscopy techniques, which the dislocations themselves are protected from nonradiative recombination events by local potentials for the violet InGaN LEDs, under the conditions of these experiments. 6 This property leaves them inactive in carrier recombination, unless these potentials are screened by carriers at higher injection levels.…”
Section: Dislocation Related Droop In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
“…Some previous work pointed out that defect recombination could be viewed as consistent with the droop behavior in the LEDs, however. 4,5 At injection conditions close to the peak of the LED efficiency curve (like external quantum efficiency vs current density, often called the LI-curve), the injected carriers are generally viewed as largely localized and, thus, immune to the major non-radiative defect recombination at dislocations. At high injection the localization potentials are screened, and the carriers are free to move to defect sites.…”
Section: Dislocation Related Droop In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
“…1) Although the origin of the efficiency droop is still the subject of controversy, [1][2][3][4] many studies suggest that it could originate from efficient Auger recombination of charge carriers confined in the quantum well (QW) plane. 2) One natural way to decrease the efficiency of Auger recombination is to decrease the charge carrier density in the QW, which can be achieved by increasing the thickness of the QW.…”
Section: Introductionmentioning
confidence: 99%
“…(1) The process of phonon-assisted hole transport contributes via tunneling at defect sites. 33 This process can be excluded here since it is insensitive to the carrier density. (2) The Auger process induces hot carriers that may relax to the defect states.…”
mentioning
confidence: 99%